Perancangan Card Game Lingkaran Kebiasaan dengan Ilustrasi Komik Strip pada Kehidupan Sehari-hari Remaja - Mohammad Candra Al-Aliyyu; Restu Ismoyo Aji; Mahimma Romadhona (IAI Nasional Laa Roiba Bogor, 2026)
Habits are behaviors formed through repetition and are often performed automatically in everyday life. In late adolescence (18–21 years), the process of habit formation is strongly influenced by the social environment, but based on the results of FGDs and questionnaires, adolescents are not yet fully aware of the habit patterns they are experiencing and how to change them. This design aims to design a card game entitled